IMPLEMENTASI STRATEGI PEMBELAJARAN BERBASIS LITERASI DALAM MENINGKATKAN KEMAMPUAN MEMBACA PEMAHAMAN SISWA KELAS III SEKOLAH DASAR - Siti Fansuri Hardianti; Haifaturrahmah; Sukron Fujiaturrahman (Pendas : Jurnal Ilmiah Pendidikan Dasar, 2025)
This study aims to describe the implementation of literacy-based learning strategies to improve reading comprehension skills of third-grade students in elementary school. This study used a qualitative descriptive approach. The participants involved the third-grade teacher and students. Data were collected through observation, interviews, and documentation. The results showed that the implementation of literacy-based learning strategies was carried out through pre-reading activities, the use of various text media, and teacher guidance in understanding reading content. The strategy has shown improvements in students’ interest in reading, their ability to answer text-based questions, and their confidence in expressing ideas related to reading materials. Therefore, literacy-based learning strategies can effectively improve elementary students’ reading comprehension skills. Keywords: Literacy, Reading Comprehension, Learning Strategy, Elementary School